Experimental continuous-variable cloning of partial quantum information - Leuchs, Gerd; et al. (Physical Review A, 2008)
The fidelity of a quantum transformation is strongly linked with the prior partial information of the state to be transformed. We illustrate this interesting point by proposing and demonstrating the superior cloning of coherent states with prior partial information. More specifically, we propose two simple transformations that under the Gaussian assumption optimally clone symmetric Gaussian distributions of coherent states as well as coherent states with known phases. Furthermore, we implement for the first time near-optimal state-dependent cloning schemes relying on simple linear optics and feedforward. © 2008 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.experi_3